Electoral reform at work : local politics and national parties, 1832-1841 - Salmon, Philip, 1968- (Royal Historical Society studies in history. New series., 2002)
The Reform Act of 1832 set in motion the political transformation of Britain. Drawing on hitherto neglected local archives, Dr Salmon demonstrates how the practical details of this extensively debated Parliamentary reform, aided by the workings of the New Poor Law (1834) and Municipal Corporations Act (1835), had a profound impact on borough and county politics, laying the constitutional foundations for the representative democracy of the Victorians.